2022
DOI: 10.1037/pst0000443
|View full text |Cite
|
Sign up to set email alerts
|

“Therapy can be restorative, but can also be really harmful”: Therapy experiences of QTBIPOC clients.

Abstract: Research suggests that queer and/or trans Black people, Indigenous people, and other People of Color (QTBIPOC) generally experience higher levels of psychological distress and depression, leading to poorer mental health outcomes (e.g., Lim & Hewitt, 2018; Sutter et al., 2018). However, little is known about the experiences of QTBIPOC individuals in therapy. The purpose of this grounded theory study was to understand the nuanced narratives of QTBIPOC individuals in therapy. Twelve QTBIPOC individuals were inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 78 publications
2
13
0
2
Order By: Relevance
“…Therapists missed important cultural opportunities when they only engaged in superficial conversations about SGM topics, failed to recognize the significance of clients’ romantic partner (e.g., Shelton & Delgado-Romero, 2011), or discounted the impacts of societal discrimination (e.g., Welch et al, 2000). For example, in one included study (Arora et al, 2022, p. 504), a queer black woman noted how her therapist could have better attended to her identities and multiple axes of oppression by, “taking that next step, seeing how [my] identities played a role.”…”
Section: Resultsmentioning
confidence: 99%
“…Therapists missed important cultural opportunities when they only engaged in superficial conversations about SGM topics, failed to recognize the significance of clients’ romantic partner (e.g., Shelton & Delgado-Romero, 2011), or discounted the impacts of societal discrimination (e.g., Welch et al, 2000). For example, in one included study (Arora et al, 2022, p. 504), a queer black woman noted how her therapist could have better attended to her identities and multiple axes of oppression by, “taking that next step, seeing how [my] identities played a role.”…”
Section: Resultsmentioning
confidence: 99%
“…Some participants in the present study reported that they were told not to disclose their nonbinary identity in the therapeutic work. Given the push to discuss power, privilege, oppression, and identities in therapeutic work, particularly when working with marginalized communities (see Arora et al, 2022), training programs that discourage nonbinary identity disclosure are reinforcing the delegitimization of nonbinary identities and perpetuating cissexism. Faculty in training programs and clinical supervisors should be required to participate in regular nonbinary focused trainings to ensure their competence in working with and training nonbinary clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, psychotherapeutic research has begun examining the therapy experiences of clients with marginalized identities (e.g., Arora et al, 2022; Morris et al, 2020). However, the experiences of psychotherapists with marginalized identities, particularly nonbinary 1 psychotherapists, have remained relatively unexamined.…”
Section: Nonbinary Psychotherapistsmentioning
confidence: 99%
“…Essa visão não propõe mudanças estruturais, mas maior atenção para as microhabilidades (microskills) do terapeuta que facilitam o proveito do tratamento pelos clientes (p. ex. Arora et al, 2022;Brown, 2008).…”
Section: Adaptação Culturalunclassified
“…Exemplos de erros são desacreditar a experiência que o cliente tem da sua identidade e lugar social, ou limitar a oportunidade de ele descrever a sua compreensão do seu contexto (Lee et al, 2022). Desmantelar essas dimensões de opressão envolve as microhabilidades do terapeuta: a validação explícita da identidade e das experiências de opressão e o acolhimento de soluções que vem de fora da cultura do terapeuta (Arora et al, 2022). Quais microhabilidades da FAP podem ser relevantes aqui?…”
Section: Reconhecer E Resolver Problemas Enquanto Ocorrem Na Sessãounclassified